2017
DOI: 10.7185/geochemlet.1737
|View full text |Cite
|
Sign up to set email alerts
|

The solubility of heat-producing elements in Earth’s core

Abstract: The long term thermal and dynamic evolution of Earth's core depends on its energy budget, and models have shown that radioactive decay due to K and U disintegration can contribute significantly to core dynamics and thermal evolution if substantial amounts of heat-producing elements are dissolved in the core during differentiation. Here we performed laser-heated diamond anvil cell experiments and measured K and U solubility in molten iron alloy at core formation conditions. Pyrolitic and basaltic silicate melts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 26 publications
8
62
0
Order By: Relevance
“…Gessmann and Wood () suggested that temperature enhances potassium incorporation into iron alloys. This was supported experimentally by Murthy et al () and Watanabe et al (), although no obvious temperature dependence was observed in other studies (Blanchard et al, ; Corgne et al, ). In this study, the temperature influence on the potassium partitioning is investigated by conducting calculations at 3,000 and 5,000 K at the constant pressure of 20 GPa, where the compositions of silicate and metallic systems are set to (MgSiO 3 ) 16 and Fe 50 , respectively.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Gessmann and Wood () suggested that temperature enhances potassium incorporation into iron alloys. This was supported experimentally by Murthy et al () and Watanabe et al (), although no obvious temperature dependence was observed in other studies (Blanchard et al, ; Corgne et al, ). In this study, the temperature influence on the potassium partitioning is investigated by conducting calculations at 3,000 and 5,000 K at the constant pressure of 20 GPa, where the compositions of silicate and metallic systems are set to (MgSiO 3 ) 16 and Fe 50 , respectively.…”
Section: Resultssupporting
confidence: 63%
“…The amount of potassium that can be incorporated into the core is determined by its partitioning between silicate and metallic systems. A number of laboratory experiments have therefore been performed to measure the metal/silicate partitioning coefficient of potassium (e. g., Blanchard et al, ; Bouhifd et al, ; Chabot & Drake, ; Corgne et al, ; Gessmann & Wood, ; Murthy et al, ; Watanabe et al, ). However, the results scatter significantly (by four orders of magnitude) potentially due to wide variations of the potassium partitioning depending on temperature, pressure, composition, and/or oxygen fugacity.…”
Section: Introductionmentioning
confidence: 99%
“…But those same experiments (e.g., Badro et al, 2016Badro et al, , 2018Blanchard et al, 2017;Bouhifd & Jephcoat, 2011;Chidester et al, 2017;Du et al, 2017;Fischer et al, 2015;Huang & Badro, 2018;Jackson et al, 2018;Ricolleau et al, 2011;Siebert et al, 2012Siebert et al, , 2013Tsuno et al, 2013) have not observed any SiO 2 exsolution and even support that the present-day core could be undersaturated in Si and O (Brodholt & Badro, 2017). But those same experiments (e.g., Badro et al, 2016Badro et al, , 2018Blanchard et al, 2017;Bouhifd & Jephcoat, 2011;Chidester et al, 2017;Du et al, 2017;Fischer et al, 2015;Huang & Badro, 2018;Jackson et al, 2018;Ricolleau et al, 2011;Siebert et al, 2012Siebert et al, , 2013Tsuno et al, 2013) have not observed any SiO 2 exsolution and even support that the present-day core could be undersaturated in Si and O (Brodholt & Badro, 2017).…”
Section: 1029/2019gl082722mentioning
confidence: 88%
“…It is noteworthy that the uncertainties (error bars plotted only for the present data + data from Badro et al, ) are on the same order as the scatter in the data, which is statistically self‐consistent. The orange data points labeled as “This study (*)” are reanalyses of previous experiments (Blanchard et al, ).…”
Section: Methodsmentioning
confidence: 96%